Correlation Between Duration of Screen Time and Method of Handling Smartphone Towards The Incidence of De Quervain’s Syndrome among The Medical Students of Diponegoro University. - Hidayat, Indra; Setiawati, Erna; Kesoema, Tanti Ajoe; Putri, Rahmi Isma Asmara (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: Smartphone with all of its benefits make the majority of its users become too attached with the device that can fulfil their various needs. Due to its accessibility, an increase of daily screen time has also been observed which may have negative impacts on health, one of them being De Quervain’s Syndrome. De Quervain’s Syndrome is a type of Repetitive Strain Injury, affecting the thumb and wrist caused by a repetitious activity that puts burden or trauma to the aforementioned body parts. Objective: To assess the correlation between duration of screen time and method of handling smartphone towards the incidence of De Quervain’s Syndrome among the medical students of Diponegoro University. Methods: This research used an analytical-observational approach with a cross-sectional design. The subjects were 113 students from the Faculty of Medicine, Diponegoro University that were obtained using consecutive sampling method. The correlation between duration of screen time and method of handling smartphone with the incidence of De Quervain’s Syndrome were performed using Spearman’s test. Results: A weak significant correlation was observed between the average duration of screen time towards the incidence of DQS pain on the right hand based on the DQST results (p=0.11), but no significant correlation was found between the same variables on the left hand (p=0,082). There is no significant correlation between the method of handling smartphones with the incidence DQS pain based on the DQST results, both on the right (p=0.93) and left (p=0.167) hands. Conclusion: Average duration of screen time was weakly correlated with the incidence DQS pain in the right hand, but no correlation was found in the left hand, based on DQST results, among the students from the Faculty of Medicine, Diponegoro University. No correlation was observed between the method of handling smartphones and the incidence of DQS among the students from the Faculty of Medicine, Diponegoro University.